The effect of rehabilitative exercises on the flexibility of the partially dislocated shoulder of young volleyball players (Journal of the College of Basic Education, 2022)
The research aims to prepare rehabilitation exercises to rehabilitate the muscles working on the shoulder joint after suffering from partial dislocation The degree and type of injury was determined , then the sample was chosen in an intentional way The researchers prepared a flexibility test on the research sample One of the most important results he reached using the statistical bag (Tetest). There are statistically significant differences between the pre- and post-measurement in flexibility on the muscles working on the shoulder joint in favor of dimensional measurement